Evaporation fractionation in a peatland drainage network affects stream water isotope composition. Issue 1 (25th January 2017) - Sprenger, Matthias; Tetzlaff, Doerthe; Tunaley, Claire; Dick, Jonathan; Soulsby, Chris
Abstract: There is increasing interest in improving understanding of evaporation within a catchment for an enhanced representation of dominant processes in hydrological models. We used a dual‐isotope approach within a nested experimental design in a boreal catchment in the Scottish Highlands (Bruntland Burn) to quantify the spatiotemporal dynamics of evaporation fractionation in a peatland drainage network and its effect on stream water isotopes. We conducted spatially distributed water sampling within the saturated peatland under different wetness conditions. We used the lc‐excess—which describes the offset of a water sample from the local meteoric water line in the dual‐isotope space—to understand the development of kinetic fractionation during runoff in a peatland network. The evaporation fractionation signal correlated positively with the potential evapotranspiration and negatively with the discharge. The variability of the isotopic enrichment within the peatland drainage network was higher with higher potential evapotranspiration and lower with higher discharge. We found an increased evaporation fractionation toward the center of the peatland, while groundwater seepage from minerogenic soils influenced the isotopic signal at the edge of the peatland. The evaporation signal was imprinted on the stream water, as the discharge from a peatland dominated subcatchment showed a more intense deviation from the local meteoric water line than the discharge from the Bruntland Burn. The findings underline that evaporation fractionation within peatland drainage networks affects the isotopic signal of headwater catchments, which questions the common assumption in hydrological modeling that the isotopic composition of stream waters did not undergo fractionation processes. Key Points: Kinetic isotopic fractionation in peatland drainage correlates positively with potential evapotranspiration and negatively with discharge The interplay between the precipitation, evaporation, hydrologic connectivity, and groundwater explains the isotopic fractionation signal The isotopic enrichment within the peatland drainage network is imprinted on the stream water